Financial Performance dan Financial Distress Perusahaan Transportasi Sebelum dan Selama Pandemi Covid-19 - Dimas Dwi Oktavian Dimas Dwi Oktavian; Diyah Probowulan Diyah Probowulan; Rendy Mirwan Aspirandi Rendy Mirwan Aspirandi (LPPM POLITEKNIK LP3I BANDUNG, 2023)
Currently, various countries have been hit by the Covid-19 outbreak, one of which is Indonesia. In this case, the government is trying to implement various policies to prevent the transmission of the epidemic. One of them is a major social disaster (PSBB) which resulted in a decrease in the number of passengers for transportation companies due to limited community mobility. This has an effect on increasing income so that it also affects the company's financial condition. Both in terms of financial performance with the ratios used, namely ROA, ROE, and NPM as well as the potential to experience financial distress with the Springate model, so it is necessary to conduct research to test and analyze financial performance and financial difficulties in transportation companies before and congratulations on the covid-19 pandemic. Because this will have an impact on stakeholder decisions in decision making caused by the presence or negative information from the company's financial condition. So in this case, a different test was carried out on the second variable above to see the difference before and during the covid-19 pandemic. The results of the Wilcoxon signed ranks test on the ROA, ROE, and NPM ratios, because the data are not normally distributed have very significant results, and the paired sample t-test because the data is normally distributed in the springate model has very significant results. So, there is a difference between before and during the covid-19 pandemic in transportation companies in terms of financial performance and financial distress.